ANEKA JENIS PENELITIAN PENDIDIKAN - Sera Yuliantini; Umar Sulaiman (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This research examines various types of educational research using literature review methods, the results of which can be found that each type of research has different characteristics and objectives, which are important to understand in the context of selecting the right type of research. Qualitative research focuses on in-depth understanding of social phenomena through interviews, observation, and text analysis, while quantitative uses numerical data to test hypotheses through statistics and measurement. Library research examines written sources such as books, articles and journals to collect information, while field research collects data directly from locations or subjects through observation and interaction. Pure science research aims to increase knowledge without thinking about practical applications, applied science uses knowledge to solve real problems and applications. Descriptive research describes the characteristics of a phenomenon or population, correlative research analyzes the relationship between two or more variables without concluding cause and effect, comparative research compares two or more groups to find differences or similarities. Overall, all types of research play an important role in developing scientific knowledge and solving practical problems. Choosing the right method not only increases the validity of the results, but also ensures that the research can make a significant contribution to understanding and innovation in various fields.